Effectiveness of Socio-Scientific Issue (SSI) Based Science E-Modules to Increase Students' Scientific Literacy - Muntari Muntari; Baiq Fitri Rahmayanti; Yayuk Andayani (Postgraduate, University of Mataram, 2024)
An important component in the learning process is the existence of teaching materials for students. Teachers need a variety of teaching materials, both in the form of textbooks and modules that can help carry out the learning process well. This research aims to test the effectiveness of a Socio-Scientific Issue (SSI) based science e-module to increase students' scientific literacy. This type of research is quasi-experimental research with a One Group Pretest-Posttest Design. The research was conducted in three class VII MTs Nurul Iman Dasan Makam, Sukamulia District, East Lombok Regency. The effectiveness of the e-module is obtained by providing test questions at the beginning (pretest) and at the end (posttest) of learning to measure the increase in students' scientific literacy. The results of the analysis of the effectiveness of increasing scientific literacy are in the medium category with an average N-gain score of 0.47. The research results show that the implementation of the SSI-based science e-module is quite effective in increasing students' scientific literacy so that it can be used as a teaching material for science learning